2012
DOI: 10.1093/rpd/ncs205
|View full text |Cite
|
Sign up to set email alerts
|

An optimal measuring timetable for thoron measurements by using Lucas scintillation cell

Abstract: Up to now, several different timetables have been proposed for thoron ((220)Rn) measurements by using the Lucas scintillation cell. In this study, based on the measuring principle, the uncertainty of the measurements was theoretically studied by using a self-developed simulation program. The results showed that a measuring timetable of 1-min consecutive counting lasted for 10 times was an optimal routine for (220)Rn measurements. Compared with the previously proposed timetables, the new measuring timetable cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…Our results presented in Table 2 indicated a very similar performance of the scintillation cell used in our study due to the similarity between the devices. Our previous study estimated the relative standard uncertainty of the grab-sample scintillation cell to be around 24% when the concentration of 220 Rn was 1,000 Bq m -3 and the concentration of 222 Rn was 50 Bq m -3 [20], which was in accordance with the findings presented in Table 3. Those consistent findings suggested the reliability of the result presented in Table 2 and Table 3.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results presented in Table 2 indicated a very similar performance of the scintillation cell used in our study due to the similarity between the devices. Our previous study estimated the relative standard uncertainty of the grab-sample scintillation cell to be around 24% when the concentration of 220 Rn was 1,000 Bq m -3 and the concentration of 222 Rn was 50 Bq m -3 [20], which was in accordance with the findings presented in Table 3. Those consistent findings suggested the reliability of the result presented in Table 2 and Table 3.…”
Section: Discussionsupporting
confidence: 89%
“…This study compared the performance of the airflow-through scintillation cell, grabsample scintillation cell, and PIPS device in terms of their lower detection limit and measurement uncertainty, which offered valuable insights into the comparative advantages of the airflow-through scintillation cell method. Previous studies have estimated the lower detection limit and measurement uncertainty of the grab-sample scintillation cell using similar devices [18,20]. Zhang et al reported a lower detection limit (at the 95% confidence interval) of 303 Bq m -3 , 404 Bq m -3 , 584 Bq m -3 and 1074 Bq m -3 for the grab-sample scintillation cell when the interfering radon concentration was 0 Bq m -3 , 50 Bq m -3 , 200 Bq m -3 , 1,000 Bq m -3 respectively [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these detectors, scintillation cells have gained widespread popularity owing to their high sensitivity and simplicity of use [14][15][16][17]. The thoron measurement methods employing scintillation cells can be classified into three types: (1) the grab-sample method initially developed by Hutter [15] and subsequently improved by others [16][17][18][19][20]; (2) the delayed-coincidence method proposed by Giffin et al [21] and further developed by others [22][23][24][25]; and (3) the airflow-through method, which is commonly used for radon measurement but less studied for thoron measurement [26][27][28]. Although the grab-sample method and the delayedcoincidence method offer an advantage over the airflow-through method as they can distinguish between thoron and radon, this disadvantage of the airflow-through method could be overcome as further elaborated in the Discussion section.…”
Section: Introductionmentioning
confidence: 99%